A Case of Combined Septic and Obstructive Shock: Usefulness of Bedside Integrated Cardiothoracic Emergency Ultrasonography. (23rd May 2013) - Zanobetti, Maurizio; De Villa, Eleonora; Lazzeretti, Delia; Conti, Alberto; Pini, Riccardo
Abstract : A 59-year-old woman presented at the emergency department with cough and weakness that started a few days before. She had a history of breast cancer treated with mastectomy with negative followup. Physical examination revealed tachycardia and tachypnea, normal blood pressure, lower lobe crackles bilaterally, and jugular venous distention. Laboratory data underlined neutrophilic leukocytosis, mild renal failure, and high procalcitonin. Chest radiography revealed bilateral nodular lesions, presumably secondary. Patient was treated with fluid therapy and broad-spectrum antibiotic therapy because of suspected sepsis. In clinical revaluation patient showed systolic hypotension unresponsive to fluid resuscitation. Because of suspected pulmonary embolism an echocardiography was performed revealing normal dimensions of right ventricle with presence of a hypoechoic mass involving tricuspid annulus and obstructing the opening of anterior tricuspid flap; inferior vena cava appeared dilated and not collapsible. Subsequently, chest ultrasonography was performed, confirming multiple rounded lesions involving the pleura bilaterally, compatible with metastasis, and absence of interstitial syndrome. Finally a computed tomography scan of chest excluded pulmonary embolism and confirmed the presence of the obstructive mass responsible for hemodynamic instability together with pulmonary sepsis.